Recent advances in the use of screen-printed electrodes in drug analysis: A review - Kelíšková, Pavlína; Matvieiev, Oleksandr; Janíková, Lenka; Šelešovská, Renáta (Elsevier Science BV, 2023)
This review discusses the recent significant advancements over the past three years (i.e., 2021-2023) in the application of screen-printed electrodes (SPE) in drug analysis. SPE gained considerable interest due to their simplicity, affordability, and versatility. The review covers unmodified and modified SPE and highlights their potential in determining of pharmaceuti-cals, including narcotics, psychotropic agents, antidiabetic medications, anti-inflammatory drugs, antibiotics, and chemo-therapeutics. Unmodified SPE provide rapid drug screening and detection, aid in forensic analysis, and contribute to the fight against drug proliferation. SPE modified with various nanomaterials, polymers, composites, and biomolecules enhance the sensitivity and selectivity of the electrodes, enabling precise analysis of drugs in samples with a complex matrix. The review summarizes the achievements of SPE for medical or forensic purposes and quality control of pharma-ceutical products.
Nedávné pokroky v použití sítotiskových elektrod při analýze léků: Přehledový článek
Keywords: Screen-printed electrodes; Modification; Drugs analysis; Forensic application; Medical application; Pharmaceutical quality control; Sítotiskové elektrody; Modifikace; Analýza léků; Forenzní aplikace; Medicínské aplikace; Kontrola kvality léčiv